Understanding the importance of the work of administrative servants at EPT from a freirian perspective (Research, Society and Development, 2022)
This article investigates, in exploratory research, the relevance of the performance of administrative servants in the preparatory phase of electronic trading in federal institutions of professional and technological education, under the socio-political-cultural approach of Paulo Freire, due to its emphasis on the human being as a subject transforming reality itself. Following are considerations about the current bidding legislation, aiming at a better connection to the proposed debate. A brief history of freirean influences on general, professional and technological education is reassembled. With Marx, in the Instructions for Delegates of the Provisional General Council (1866), Gramsci and his Cadernos do Carcere (2001), the text connects Freire to these references and to the EPT in Brazil. More freirean contributions to EPT are demonstrated, relating them to the principles, guidelines and norms that govern this type of education. The applicability of Freire's theories is verified to achieve the objective of this bibliographic survey, that is, to understand the investigated reality, from a human and professional perspective and, if necessary, to propose improvements. The study seeks to answer the questions raised in the introduction, recognizes Freire's contribution to the entire context of the EPT and the importance of the work carried out by the administrative area in question in the construction of quality education, suggests a permanent work of management to connect the areas means and end of institutions to the common purpose of integrality in education and makes other propositions.